2018
DOI: 10.3389/fendo.2018.00225
|View full text |Cite
|
Sign up to set email alerts
|

Use of Readily Accessible Inflammatory Markers to Predict Diabetic Kidney Disease

Abstract: Diabetic kidney disease is a common complication of type 1 and type 2 diabetes and is the primary cause of end-stage renal disease in developed countries. Early detection of diabetic kidney disease will facilitate early intervention aimed at reducing the rate of progression to end-stage renal disease. Diabetic kidney disease has been traditionally classified based on the presence of albuminuria. More recently estimated glomerular filtration rate has also been incorporated into the staging of diabetic kidney di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 147 publications
(157 reference statements)
1
43
0
2
Order By: Relevance
“…An increase in urinary albumin excretion is a clinical manifestation for DN, starting from microalbuminuria to macroalbuminuria and eventually ESRD [8,9]. Current diagnosis of DN is depended on albuminuria as a biomarker [11]. However, its diagnostic value in early-stage DN is limited because renal injury commonly precedes urinary albumin secretion [6].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in urinary albumin excretion is a clinical manifestation for DN, starting from microalbuminuria to macroalbuminuria and eventually ESRD [8,9]. Current diagnosis of DN is depended on albuminuria as a biomarker [11]. However, its diagnostic value in early-stage DN is limited because renal injury commonly precedes urinary albumin secretion [6].…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] Some other biomarkers, such as α1-microglobulin (α1-MG), β2-microglobulin (β2-MG), inflammatory markers (e.g., C-reactive protein, interleukin-6, and tumor necrosis factor-α), as well as several angiogenic and anti-angiogenic factors (e.g., vascular endothelial growth factor (VEGF), VEGF receptors, angiopoietins and endostatin) were reported to play important roles in early detection, therapeutic prevention and implementation of DKD. [3638] Plasma tumor necrosis factor receptor-1 (TNFR-1), TNFR-2, and kidney injury molecule-1 (KIM-1) were independently associated with higher risk of eGFR decline in patients with early or advanced DKD. [39,40] The research in “biomarker” should still be a direction in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Although studies have shown a positive relationship between CRP and diabetes, this association is often reduced or attenuated completely when anthropometric body measures, such as body mass index and hip-waist ratio, are accounted for in the analyses [ 25 ]. In our study, however, we found that the association between CRP and T2DM was robust for both Blacks and Whites ( Table 3 ], and notably stronger among Whites than Blacks even when waist circumference was added to the models.…”
Section: Discussionmentioning
confidence: 99%